PHILOSOPHICAL-HISTORICAL ANALYSIS OF THE RUSSIAN NATIONAL DOCTRINE AS AREA OF SAMOROZVITKU OF SUBJECTIVE SPIRIT OF RUSSIANS - Сергеєв, М. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Basic maintenance of the Russian national doctrine, counted on a long-term prospect maintenance of the Russian national idea is represented in which opens up in the article.